Influence of packaging design parameters on customers’ decision-making process - Malešević, Minja; Stančić, Mladen (Journal of Graphic Engineering and Design, 2021)
Many recent research has focused on graphic design and shape of the packaging, and their effects on the customer’s decision-making process as two separate categories. Since the shape of the packaging along with the graphic design plays an important role in the visual appearance of the packaging and attracts the customer’s attention, the main objective of this research was to find out which packaging shapes and graphic elements customers find most attractive, as well as to understand the general opinion of customers about the influence of packaging aesthetics on their decision-making process when purchasing a product. Methodology of this research was conducted in two stages, from which the first one included creating three different graphic design solutions combined with three shape categories, and three variations of added value, for the same food packaging. The second part of the research covered an online questionnaire, in which a group of 50 people participated. This questionnaire focused on three variables: graphic design of the packaging, packaging shape and it’s added value. These variables were evaluated using the Likert scale. Through the questionnaire, participants were asked to answer general questions about the impact of the packaging visual appearance and added value, on their decision-making process when buying a product, as well as to choose the most appealing packaging between the given options. The research results showed that customers preferred non-standard packaging shapes and simple graphic design, as well as packaging with added value. The results of this research prove that the aesthetics of packaging has an impact on the customer’s perception of a product, which means that packaging plays an important role in product marketing. Article history: Received (June 14, 2021); Revised (September 26, 2021); Accepted (October 5, 2021); Published online (December 1, 2021)